2015
DOI: 10.1186/s13287-015-0016-2
|View full text |Cite
|
Sign up to set email alerts
|

Culture of human mesenchymal stem cells using a candidate pharmaceutical grade xeno-free cell culture supplement derived from industrial human plasma pools

Abstract: IntroductionFetal bovine serum (FBS) is an animal product used as a medium supplement. The animal origin of FBS is a concern if cultured stem cells are to be utilized for human cell therapy. Therefore, a substitute for FBS is desirable. In this study, an industrial, xeno-free, pharmaceutical-grade supplement for cell culture (SCC) under development at Grifols was tested for growth of human mesenchymal stem cells (hMSCs), cell characterization, and differentiation capacity.MethodsSCC is a freeze-dried product o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 44 publications
2
51
1
2
Order By: Relevance
“…Also, highly proliferative hBM‐MSCs exhibit better engraftment in preclinical mice models . The hBM‐MSCs in the current study had a similar PDT (76.5 ± 34 hours) as observed in previous studies . We further observed that hBM‐MSC cultures enriched in small cell and nuclei exhibited greater proliferative capacity.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Also, highly proliferative hBM‐MSCs exhibit better engraftment in preclinical mice models . The hBM‐MSCs in the current study had a similar PDT (76.5 ± 34 hours) as observed in previous studies . We further observed that hBM‐MSC cultures enriched in small cell and nuclei exhibited greater proliferative capacity.…”
Section: Discussionsupporting
confidence: 87%
“…The AUC of cell proliferation curves was generally used as a good metric to summarize the growth curve . Nevertheless, we also calculated the average value of PDT for all donor cells (76.5 ± 34 hours), which was similar to previously reported PDT for primary hBM‐MSCs (between 72 and 120 hours) . Furthermore, we found a strong negative correlation between AUC and PDT values for analyzed cell populations ( r s = −0.73, P < .0001, n = 53, Figure S2A).…”
Section: Resultssupporting
confidence: 76%
“…Human plasma‐derived supplement for cell culture medium (SCC), produced by the pharmaceutical company Grifols (Parets del Valles, Spain), was recently described as a potential candidate for xeno‐free supplementation of hMSCs expansion media (Diez, Bauman, Gajardo, & Jorquera, ). Besides being a pharmaceutical‐grade product, SCC has the advantages of (a) providing uniformity between batches, because it is obtained from human plasma pools of over 1,000 donors and (b) be safe, which is assured by every individual donation testing for viral markers and pathogenic agents and by steps with viral clearance capacity during its production process (Diez et al, ; Nieto JIJ & Diez, ). Moreover, SCC is a GMP‐compliant product, being every step of its development well‐defined and validated under standard operating procedures.…”
Section: Introductionmentioning
confidence: 99%
“…This work aimed to optimize the use of a pharmaceutical grade xeno‐free strategy, based on SCC‐supplemented medium (Diez et al, ) to improve the expansion of hMSCs for clinical applications.…”
Section: Introductionmentioning
confidence: 99%
“…In Díez et al [50], commercial bone marrow-derived hMSC were expanded in the same medium used here but with additional platelet lysate and fibroblast growth factor. Platelet lysate supplementation is controversial, and its effect on immunomodulatory MSC properties is not clear, with some studies showing that it reduces hMSC immunosuppressive properties [40, 41, 61, 66].…”
Section: Discussionmentioning
confidence: 99%